Mesra kasih bersama komuniti OKU / Azila Ayob, Norazlin Abd Aziz and Nor Syamaliah Ngah - Ayob, Azila; Abd Aziz, Norazlin; Ngah, Nor Syamaliah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
We can easily understand that disabled people can best be described as people who have physical or mental impairment that substantially limits their major life activities. Nevertheless, they are also part of the community members who have feelings, abilities, skills, talents and intelligence in various fields like other normal human beings. The United Nations approved the Convention on the Rights of Persons with Disabilities (CRPD) on 13 December 2006, and Malaysia signed it on 8 April 2008. This convention aspires to serve as a human rights instrument in order to guarantee that people with disabilities (OKU) have equal rights in society and to safeguard them from damage, violence, and abuse. This convention also underlines the importance of providing disabled individuals with unrestricted access so they can fully participate in society.